2019
DOI: 10.1136/annrheumdis-2018-214514
|View full text |Cite
|
Sign up to set email alerts
|

Prevotella copri in individuals at risk for rheumatoid arthritis

Abstract: ObjectivesRheumatoid arthritis (RA) has been associated with a relative expansion of faecal Prevotellaceae. To determine the microbiome composition and prevalence of Prevotella spp. in a group of individuals at increased risk for RA, but prior to the development of the disease.MethodsIn an ongoing cohort study of first-degree relatives (FDRs) of patients with RA, we identified ‘FDR controls’, asymptomatic and without autoantibodies, and individuals in pre-clinical RA stages, who had either developed anticitrul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
237
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 310 publications
(248 citation statements)
references
References 20 publications
9
237
1
1
Order By: Relevance
“…In humans, sequencing studies showed differences in the gut microbiome of RA patients and healthy individuals, with a special focus on the bacterium Prevotella copri ( Pc ), which was found to be relatively abundant in the gut of early RA patients . Prevotella species were furthermore found to be abundant in the gut of at‐risk individuals . Although it was hypothesized that one of Pc's antigens could be citrullinated and targeted by ACPA, at the moment there is a lack of conclusive data linking Pc with AMPA.…”
Section: Hypotheses Elucidating Mechanisms Of Autoimmunity In Ramentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, sequencing studies showed differences in the gut microbiome of RA patients and healthy individuals, with a special focus on the bacterium Prevotella copri ( Pc ), which was found to be relatively abundant in the gut of early RA patients . Prevotella species were furthermore found to be abundant in the gut of at‐risk individuals . Although it was hypothesized that one of Pc's antigens could be citrullinated and targeted by ACPA, at the moment there is a lack of conclusive data linking Pc with AMPA.…”
Section: Hypotheses Elucidating Mechanisms Of Autoimmunity In Ramentioning
confidence: 99%
“…143,145 Prevotella species were furthermore found to be abundant in the gut of at-risk individuals. 146 Although it was hypothesized that one of Pc's antigens could be citrullinated and targeted by ACPA, 147 at the moment there is a lack of conclusive data linking Pc with AMPA.…”
Section: Microbiome and Citrullinated Antigensmentioning
confidence: 99%
“…More recently, patients at risk of RA showed an enrichment of Prevotella spp. in stools samples compared with controls .…”
Section: Phase 2: Preclinical Ramentioning
confidence: 99%
“…In addition, high levels of genomic diversity within Prevotella strains of the same species have been observed ( 3 ), which adds another layer of complexity for predicting the effects of Prevotella strains. Recent studies have linked higher intestinal abundance of P. copri to rheumatoid arthritis ( 4-6 ), metabolic syndrome ( 7 ), low-grade systemic inflammation ( 7 ) and inflammation in the context of human immunodeficiency virus (HIV) infection ( 8-10 ), suggesting that some Prevotella strains may trigger and/or worsen inflammatory diseases ( 1, 11, 12 )…”
Section: Introductionmentioning
confidence: 99%